Computed tomography and radiography in the diagnosis and followup of periprosthetic osteolysis after total ankle arthroplasty - Kohonen, Ia (Annales Universitatis Turkuensis D 1272, 2017)
Periprosthetic osteolysis is one of the most significant long-term complications after total ankle arthroplasty (TAA). The exact pathogenesis of osteolysis is unclear. It is a biological process involving many factors, mechanical factors probably, as well. Osteolysis is a progressive phenomenon which may lead to component failure. Traditionally, patients with an ankle prosthesis are monitored only by radiography. In this study the incidence of periprosthetic osteolysis around TAAs was evaluated by radiographs and computed tomography (CT). These two methods were also compared for detection of osteolytic lesions around the prosthesis components. Acquisition parameters and positioning were studied for optimal imaging of total ankle prostheses on CT. TAAs were monitored by CT after bone grafting of osteolytic lesions and also the patients’ symptoms after bone grafting were evaluated. Early-onset TAA-associated periprosthetic osteolysis was common after arthroplasty. CT showed more and larger periprosthetic osteolytic lesions than radiographs around TAAs, especially around the talar component. CT proved to be a reliable imaging modality for studying periprosthetic lesions adjacent to ankle prostheses. Image artifacts on CT caused by the metal prosthesis components were small when acquisition parameters and, especially, orientation of the prosthesis in relation to the x-ray tube were optimal. Radiologically, progression of osteolysis continued in spite of bone grafting of periprosthetic osteolytic lesions around TAAs. We recommend adding ankle CT to the postoperative follow-up for patients with suspected or known periprosthetic osteolytic lesions on radiographs. CT is also useful when evaluating periprosthetic bone stock before a reoperation.

Nilkan tekoniveleen liittyvän osteolyysin diagnostiikka ja seuranta tietokonetomografia- ja rtg-kuvauksella Tekonivelen ympärille ilmaantuva osteolyysi on merkittävimpiä nilkan tekonivelleikkauksen myöhäisvaiheen komplikaatioita. Osteolyysin patogeneesiä ei täysin tunneta. Se on monitekijäinen biologinen prosessi, johon myös mekaaniset tekijät vaikuttavat. Osteolyysi on etenevä prosessi, joka pahimmillaan johtaa tekonivelen irtoamiseen. Potilaita, joilla on nilkan tekonivel, on perinteisesti kuvannettu ainoastaan natiiviröntgenkuvilla. Tässä tutkimuksessa nilkan tekonivelen ympärillä esiintyvää osteolyysiä tutkittiin röntgen- ja tietokonetomografiakuvauksella (TT); näitä kuvantamismenetelmiä myös verrattiin toisiinsa osteolyysimuutosten havaitsemisessa. Sen lisäksi etsittiin optimaalisia kuvausparametreja ja -asentoa ajatellen nilkan tekonivelen TT-kuvausta. Nilkan tekoniveliä seurattiin TT-kuvauksella osteolyysimuutosten luusiirretäytön jälkeen. Lisäksi potilaiden kliinisiä oireita tarkasteltiin näiden uusintaleikkausten jälkeen. Nilkan tekonivelten ympärillä havaittiin runsaasti osteolyysiä jo varsin varhaisessa vaiheessa tekonivelleikkauksen jälkeen. TT-kuvaus havaitsi enemmän ja kookkaampia muutoksia kuin röntgenkuvaus. Erityisesti telaluussa olevien osteolyysimuutosten arvioinnissa TT-kuvaus osoittautui hyödylliseksi kuvantamismenetelmäksi. TT-kuvaus oli luotettava kuvattaessa tekonivelen ympärillä olevia osteolyysimuutoksia. Metalliosien aiheuttamat artefaktat TT-kuvissa jäivät vähäisiksi, kun kuvausparametrit ja erityisesti tekonivelen asento suhteessa kuvausputkeen olivat optimaaliset. Osteolyysimuutosten luusiirretäytön jälkeen osteolyysin radiologinen progressio oli tavallista. Nilkan tekonivelen TT-kuvaus on suositeltavaa potilaille, joiden röntgenkuvissa on todettu tai epäilty osteolyysiä tekonivelen ympärillä. TT-kuvaus on myös hyödyllinen arvioitaessa luurakennetta tekonivelen ympärillä ennen uusintaleikkausta.